The nexus of informatisation and internationalisation: a new stage in the internationalisation of labour. (1st July 2007) - Andreas Boes; Tobias Kämpf
Abstract : For a long time, it was the mainstream view that the internationalisation of labour is limited primarily to industrial manufacturing. However there are now signs that service employmrnt, or more precisely, information work, has also become a focus of globalisation. As a result, a new phase of informatisation has arisen, characterised by the rise of the internet as a new global space of action and new opportunities for an international division of labour For almost any activity comprising work with digitised information, global information networks have created a new, globally accessible space of production. By this means, geographical distances can be bridged in real time in many labour processes. The dynamics of this development are illustrated in this paper by the IT Industry and the rise of India to a new strategic position as a site for IT development, drawing on interviews carried out in India and Germany by the 'Export IT' project (www.export-it.de ).